At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To find the equation of the graph of the function [tex]\( y = x^2 \)[/tex] reflected over the [tex]\( x \)[/tex]-axis, we need to understand what reflecting a graph over the [tex]\( x \)[/tex]-axis entails. Reflecting a graph over the [tex]\( x \)[/tex]-axis means that each point on the graph (that has the form [tex]\((x, y)\)[/tex]) will be transformed to a new point [tex]\((x, -y)\)[/tex].
Let's start with the original function [tex]\( y = x^2 \)[/tex]:
- For any point [tex]\((x, y)\)[/tex] on this graph, the [tex]\( y \)[/tex]-coordinate is given by [tex]\( y = x^2 \)[/tex].
When we reflect this graph over the [tex]\( x \)[/tex]-axis:
- The [tex]\( x \)[/tex]-coordinate remains the same.
- The new [tex]\( y \)[/tex]-coordinate becomes the negative of the original [tex]\( y \)[/tex]-coordinate.
Therefore, the new [tex]\( y \)[/tex]-coordinate will be:
[tex]\[ y = - (x^2) \][/tex]
or simply,
[tex]\[ y = -x^2 \][/tex]
Thus, the equation of the transformed graph, which is the reflection of [tex]\( y = x^2 \)[/tex] over the [tex]\( x \)[/tex]-axis, is:
[tex]\[ y = -x^2 \][/tex]
Let's examine the given options to identify which one matches our result:
1. [tex]\( y = -x^2 \)[/tex]
2. [tex]\( y = (-x)^2 \)[/tex]
3. [tex]\( y = \sqrt{-x} \)[/tex]
4. [tex]\( y = -\sqrt{x} \)[/tex]
The correct option is:
[tex]\[ \boxed{y = -x^2} \][/tex]
This matches the equation we determined for the graph after reflection over the [tex]\( x \)[/tex]-axis.
Let's start with the original function [tex]\( y = x^2 \)[/tex]:
- For any point [tex]\((x, y)\)[/tex] on this graph, the [tex]\( y \)[/tex]-coordinate is given by [tex]\( y = x^2 \)[/tex].
When we reflect this graph over the [tex]\( x \)[/tex]-axis:
- The [tex]\( x \)[/tex]-coordinate remains the same.
- The new [tex]\( y \)[/tex]-coordinate becomes the negative of the original [tex]\( y \)[/tex]-coordinate.
Therefore, the new [tex]\( y \)[/tex]-coordinate will be:
[tex]\[ y = - (x^2) \][/tex]
or simply,
[tex]\[ y = -x^2 \][/tex]
Thus, the equation of the transformed graph, which is the reflection of [tex]\( y = x^2 \)[/tex] over the [tex]\( x \)[/tex]-axis, is:
[tex]\[ y = -x^2 \][/tex]
Let's examine the given options to identify which one matches our result:
1. [tex]\( y = -x^2 \)[/tex]
2. [tex]\( y = (-x)^2 \)[/tex]
3. [tex]\( y = \sqrt{-x} \)[/tex]
4. [tex]\( y = -\sqrt{x} \)[/tex]
The correct option is:
[tex]\[ \boxed{y = -x^2} \][/tex]
This matches the equation we determined for the graph after reflection over the [tex]\( x \)[/tex]-axis.
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.